2004
DOI: 10.1016/j.bbamcr.2003.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of MAP kinase-like proteins mediate the response of the halotolerant alga Dunaliella viridis to hypertonic shock

Abstract: The microalga Dunaliella viridis has the ability to adapt to a variety of environmental stresses including osmotic and thermal shocks, UV irradiation and nitrogen starvation. Lacking a rigid cell wall, Dunaliella provides an excellent model to study stress signaling in eukaryotic unicellular organisms. When exposed to hyperosmotic stress, UV irradiation or high temperature, a 57-kDa protein is recognized by antibodies specific to mammalian p38, to its yeast homologue Hog1, and to the phospho-p38 MAP kinase mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 36 publications
4
47
0
Order By: Relevance
“…low and high C, low and high N, and low and high temperature. Previous findings of our group have demonstrated the existence and activation of p38-like and JNK-like MAPK cascades in both microalgae (Jiménez et al 2004, García-Gómez et al 2012) and macroalgae (Parages et al , 2013(Parages et al , 2014 in response to stress. These protein kinases play a crucial role in early response and acclimation of algae to severe environments (i.e.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…low and high C, low and high N, and low and high temperature. Previous findings of our group have demonstrated the existence and activation of p38-like and JNK-like MAPK cascades in both microalgae (Jiménez et al 2004, García-Gómez et al 2012) and macroalgae (Parages et al , 2013(Parages et al , 2014 in response to stress. These protein kinases play a crucial role in early response and acclimation of algae to severe environments (i.e.…”
Section: Discussionmentioning
confidence: 60%
“…Despite the fact that the study of signal transduction in algae is very recent, different studies with both macro-and microalgae (Jiménez et al 2004, 2007, García-Gómez et al 2012 have clearly shown the presence of p38-like, JNK-like and ERK-like components in algae, as well as their crucial role in acclimation to stress and in cell division (Jiménez et al 2004, 2007, Parages 2012. A procedure has been developed to detect the presence of these MAPK homologues in several species of Chlorophyta, Rhodophyta and Phaeophyta , revealing that phosphory lation of p38-and JNK-like MAPKs occurs in Arctic kelps in response to increasing UVR exposure and temperature (Parages et al 2013) as well as in intertidal macroalgae at the onset of emersion and during periods of the highest irradiation (Parages et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So far, p38-like and JNK-like MAPKs have been excluded from higher plants based on sequence analysis failure to recover plant homologues of TGY and TPY motifs within the activation loop of MAPKs [11]. However, recently, Jimenez et al [17] demonstrated the occurrence of a 57 kDa phospho-p38-like MAPK in hyperosmotically and UV-stressed unicellular alga Dunaliella. In our system, detection of the phosphop38-like MAPK was based on a highly specific antibody raised against the phosphorylated form of an oligopeptide containing the 180 TG 182 Y motif of mammalian p38-MAPK.…”
Section: Identification Of a Phosphorylated P38-like Mapk Inmentioning
confidence: 99%
“…In our system, detection of the phosphop38-like MAPK was based on a highly specific antibody raised against the phosphorylated form of an oligopeptide containing the 180 TG 182 Y motif of mammalian p38-MAPK. This antibody detected phospho-p38-MAPK in phylogenetically distant organisms including algae [17], mammals [18], amphibians [19,20] and mussels [21]. Additionally, antibodies raised against the similar oligopeptide of mammalian ERKs failed to detect the 46 kDa band in the plasmolyzed root cells of wheat ( Fig.…”
Section: Identification Of a Phosphorylated P38-like Mapk Inmentioning
confidence: 99%
“…In green plants calcium signalling has been shown to be involved in cell division and responses to hormones, light, pathogen elicitors and abiotic stresses (Charpenteau et al, 2004). Mitogenactivated protein (MAP) kinases are serine/threonine kinases found in all eukaryotic cells (Jime´nez et al, 2004) and they are activated by environmental stimuli such as cold shock, wounding and pathogen infection (Hardie, 1999). Wheeler et al (2008) proposed that the evolution of multicellularity requires the development of complex signalling mechanisms to regulate intercellular interactions e.g.…”
Section: Discussionmentioning
confidence: 99%